Psychedelics, Mystical Experience, and Therapeutic Efficacy: A Systematic Review - Ko, Kwonmok; Knight, Gemma; Rucker, James J.; Cleare, Anthony J. (Frontiers in Psychiatry, 2022)
The mystical experience is a potential psychological mechanism to influence outcome in psychedelic therapy. It includes features such as oceanic boundlessness, ego dissolution, and universal interconnectedness, which have been closely linked to both symptom reduction and improved quality of life. In this review, 12 studies of psychedelic therapy utilising psilocybin, ayahuasca, or ketamine were analysed for association between mystical experience and symptom reduction, in areas as diverse as cancer-related distress, substance use disorder, and depressive disorders to include treatment-resistant. Ten of the twelve established a significant association of correlation, mediation, and/or prediction. A majority of the studies are limited, however, by their small sample size and lack of diversity (gender, ethnic, racial, educational, and socioeconomic), common in this newly re-emerging field. Further, 6 out of 12 studies were open-label in design and therefore susceptible to bias. Future studies of this nature should consider a larger sample size with greater diversity and thus representation by use of randomised design. More in-depth exploration into the nature of mystical experience is needed, including predictors of intensity, in order to maximise its positive effects on treatment outcome benefits and minimise concomitant anxiety.